Duku peel ethyl acetate extract as an adjunctive treatment of doxorubicin on triple negative breast cancer 4T1 cells - Faaza Aulia Rahman; Aulia Nur Septiani; Desty Restia Rahmawati; Novia Permata Hapsari; Edy Meiyanto; Ratna Asmah Susidarti (Indonesian Journal of Biotechnology, 2025)
Triple‐negative breast cancer (TNBC) faces significant treatment challenges due to its resistance to chemotherapy and high‐rate metastatic occurrence. Adjunctive treatment is a promising approach to improve chemotherapy effectiveness while reducing toxicity on normal cells. Natural compounds of Lansium domesticum (duku) exhibit potential as adjunctive cancer treatments. This study aims to investigate the potential of duku peel extract (DPE) to be developed as an adjunctive agent. The cytotoxic activity of DPE against 4T1 cells was conducted through MTT assay, both in single and combination treatments. The anti‐migratory effect of DPE was examined by scratch wound healing assay. The molecular mechanism of DPE was confirmed using virtual screening via bioinformatics approaches, including protein target prediction and molecular docking. The results show that DPE has cytotoxic activity with an IC50 value of 47 µg/mL against the 4T1 cell line, in a 24‐hour treatment period. Interestingly, DPE not only had a good synergistic effect (mean CI value, i.e. 0.34), but also showed significant inhibition of cell migration with doxorubicin (Dox). Additionally, virtual bioinformatics screening approaches suggest the potential mechanism of DPE compound action by targeting CDC25B and TOP2A. Overall, DPE holds promise as an adjunctive treatment of Dox against 4T1 TNBC cells.